Blended Learning and Media Literacy: A New Paradigm in English Language Teaching - Shalola Rakhmonova (Scientific Trends, 2025)
Blended learning, an innovative educational approach that combines traditional face-to-face instruction with online learning, is rapidly transforming the landscape of English language teaching (ELT). This paradigm shift has been fueled by advancements in technology and the growing need for flexible, student-centered learning environments. This article explores the intersection of blended learning and media literacy in the context of ELT, highlighting the benefits of integrating digital tools and media platforms into language teaching practices. Through a review of current literature and practical case studies, the article examines how media literacy fosters critical thinking, enhances language acquisition, and equips students with the skills necessary to navigate the media-saturated world. The discussion also addresses the challenges teachers face when implementing blended learning models and media literacy initiatives, offering recommendations for effective strategies in enhancing student engagement, motivation, and language proficiency.
Keywords: Blended Learning, Media Literacy, English Language Teaching (ELT), Digital Tools, Critical Thinking, Language Acquisition, Student-Centered Learning, Educational Technology, Media Platforms, Teaching Strategies.